Time-dependent vector stabilization - Sergey Nikitin (International Journal of Mathematics and Mathematical Sciences)
The paper presents necessary and sufficient conditions for a single input system defined by a time-dependent vector to be stabilized by a linear feedback. The paper employs a new technique based on averaging along a moving time interval.